Radial artery pseudoaneurysm as a rare very late complication of transradial cardiac catheterization - Radomir Nykl; Jan Precek; Milos Spacek; Martin Sluka; Stepan Hudec; Petr Heinc; Milos Taborsky (Biomedical Papers, 2021)
Aims. Here, we report a case of very late (70+ days) development of pseudoaneurysm on the site of sheath insertion in a 60- year old woman. Methods. The patient underwent cardiac catheterization using transradial approach. Results. Despite the transradial approach, which is generally considered as a suitable prevention of this problem, and despite absence of any periprocedural complications, the patient developed a pseudoaneurysm after more than 70 days from the procedure. Conclusions. In some cases, a pseudoaneurysm may develop extremely late after cardiac catheterization. Such an extremely late development of pseudoaneurysm has not been described in literature so far.